Bio and Micro-Electronics eLearning by Online Collaborative Support. (2016) - Patrichi, Bogdan; Prelipceanu, Dan; Manuc, Daniela; Ravariu, Cristian; Babarada, Florin
Abstract: This paper reports the development of a prototype authentication system, tested for using in a graduate e-learning program. A new challenge in the biomedical engineering is the contextualized access and semantic interoperability of the electronic health records, especially in web assisted patients. Remote bioengineering is one of the future directions for advanced teleworking, e-working environments especially in the engineering and bioscience. Intelligent e-Learning tools, able to optimally complement or replace traditional instruction in certain specific and correlated domains are currently being developed. Such tools are endowed with intelligence, the capability of guiding the trainer and customising the knowledge to the learner preferences, interest and needs. Today, the microelectronics field strongly collaborates with nano-electronics, micro-mechanical systems and biodevices. The response from the students is analysed by direct feedback and the final score of the students from the last academic year at the Biodevices discipline, including the students preferred subjects.